The Influence of Think Pair Share Type of Cooperative Learning Model Toward Students Conceptual Comprehension and Mathematics Communication - Umar, Fahkrullah I Tama (Jurnal Curricula, 2018)
Think pair share (TPS) type of cooperative learning model is a useful teaching strategy to train students to reconstruct their knowledge they have learnt. It gives students time to think, respond and help each other. It has three important phases; think which means thinking problems individually;  pair which means discussing and drawing a hypothesis of a problem in pair; and share which means pairs of student share their ideas and the other students respond to their presentation in the class. The population of this research was all students of grade X at MAN Kota Padang. Problems which rise in grade X MAN Kota Padang are students low concept acquisition and mathematics comunication ability in learning mathematic. In order to overcome those problems, it was planned to apply think pair share. Therefore, this research was intended to know the influence of TPS toward the students’ concept acquisition and mathematics comunication ability. This research was quasy experimental. Data analysis used test of t test dan Mann Withney  U. Based on analysis data showed that : (1) The students’ concept acquisition and mathematics comunication ability who studied by using TPS better than those who were taught by using conventional learning.(2) The concept acquisiton and mathematics comunication of the high prior knowledge, medium prior knowledge dan the low prior knowledge of student who studied by using TPS better than those who were taught by using conventional learning. Based on the result of the study, the researcher suggest TPS cooperative learning model a considerable teaching model because it has effectively improved students’ concept acquisition and mathematics comunication ability.